PERENCANAAN ULANG STRUKTUR BANGUNAN GEDUNG PESANTREN KOTA SURABAYA - Brian Nugroho Putra; Sugeng Riyanto; Armin Naibaho (Jurusan Teknik Sipil Politeknik Negeri Malang, 2024)
Pesantren is an Islamic educational institution that uses the main building as a place to carry out its learning. The Islamic Boarding School building is designed to have 6 floors with the ground floor being the mosque. Planning is carried out using STAAD Pro Connect Edition, Autocad, Excel and Microsoft Word as auxiliary programs in this planning. The planning results show that the main beam dimensions are 40/60 with 12D19 tension reinforcement, and 6D19 compression reinforcement, 6D19 field tensile reinforcement and 3D19 compression reinforcement. For joist beams, the dimensions are 30/40 with bearing tensile reinforcement. 5D19 and press 3D19, field tension reinforcement 6D19 and press 4D19. For columns, dimensions of 60x60 are obtained with reinforcement 20D19 and stirrups 13-100, while for floor slabs a thickness of 150 mm is obtained with reinforcement in the x and y directions D12 – 150 and reinforcement for Ø8-150.